Changes in arginase activity and AST enzyme levels in the cardiac and skeletal muscle and liver of lambs with white muscle disease - Hanedan, Basak; Erisir, Mine; Kandemir, Fatih Mehmet; Ozkaraca, Mustafa (Tubitak Scientific & Technological Research Council Turkey, 2015)
The aim of this study was to evaluate arginase activity and aspartate aminotransferase (AST) levels in the tissues of the cardiac and skeletal muscle and liver of lambs with white muscle disease (WMD). The cardiac and skeletal muscle and liver tissues were obtained from 8 lambs with WMD and 9 apparently healthy lambs. The diagnosis of WMD was made with the detection of hyaline degeneration upon histopathological examination. A significant increase in arginase activity in the cardiac and skeletal muscle and liver tissues and a significant decrease in AST levels in the cardiac muscle were detected in the WMD group compared to the control group. It was concluded that increased arginase activity in cardiac and skeletal muscle and liver may enhance polyamine synthesis for the repair of cardiac and skeletal muscle injuries in lambs with WMD and that AST in the cardiac muscle might decrease due to the cardiac muscle injury.
Keywords: Arginase; aspartate aminotransferase enzyme; white muscle disease; lamb